Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve each of these logarithmic equations step-by-step:
### (a) [tex]\(\log_7 3 - \log_7 8 = \log_7 \square\)[/tex]
We use the property of logarithms that states:
[tex]\[ \log_b a - \log_b c = \log_b \left(\frac{a}{c}\right) \][/tex]
Applying this property, we have:
[tex]\[ \log_7 3 - \log_7 8 = \log_7 \left(\frac{3}{8}\right) \][/tex]
Thus, the missing value in the equation is:
[tex]\[ \square = \frac{3}{8} \][/tex]
So, (a) [tex]\(\log_7 3 - \log_7 8 = \log_7 \left(\frac{3}{8}\right)\)[/tex].
### (b) [tex]\(\log_5 2 + \log_5 \square = \log_5 14\)[/tex]
We use the property of logarithms that states:
[tex]\[ \log_b a + \log_b c = \log_b (a \cdot c) \][/tex]
Applying this property, we have:
[tex]\[ \log_5 2 + \log_5 \square = \log_5 (2 \cdot \square) \][/tex]
Given that it equals [tex]\(\log_5 14\)[/tex], we can equate:
[tex]\[ 2 \cdot \square = 14 \][/tex]
Solving for the missing value, we get:
[tex]\[ \square = \frac{14}{2} = 7 \][/tex]
So, (b) [tex]\(\log_5 2 + \log_5 7 = \log_5 14\)[/tex].
### (c) [tex]\(3 \log_3 2 = \log_3 \square\)[/tex]
We use the property of logarithms that states:
[tex]\[ n \log_b a = \log_b (a^n) \][/tex]
Applying this property, we have:
[tex]\[ 3 \log_3 2 = \log_3 (2^3) \][/tex]
Thus, the missing value in the equation is:
[tex]\[ \square = 2^3 = 8 \][/tex]
So, (c) [tex]\(3 \log_3 2 = \log_3 8\)[/tex].
### Summary of Solutions:
(a) [tex]\(\log_7 3 - \log_7 8 = \log_7 \left(\frac{3}{8}\right)\)[/tex]
(b) [tex]\(\log_5 2 + \log_5 7 = \log_5 14\)[/tex]
(c) [tex]\(3 \log_3 2 = \log_3 8\)[/tex]
We have filled in the missing values to make the equations true.
### (a) [tex]\(\log_7 3 - \log_7 8 = \log_7 \square\)[/tex]
We use the property of logarithms that states:
[tex]\[ \log_b a - \log_b c = \log_b \left(\frac{a}{c}\right) \][/tex]
Applying this property, we have:
[tex]\[ \log_7 3 - \log_7 8 = \log_7 \left(\frac{3}{8}\right) \][/tex]
Thus, the missing value in the equation is:
[tex]\[ \square = \frac{3}{8} \][/tex]
So, (a) [tex]\(\log_7 3 - \log_7 8 = \log_7 \left(\frac{3}{8}\right)\)[/tex].
### (b) [tex]\(\log_5 2 + \log_5 \square = \log_5 14\)[/tex]
We use the property of logarithms that states:
[tex]\[ \log_b a + \log_b c = \log_b (a \cdot c) \][/tex]
Applying this property, we have:
[tex]\[ \log_5 2 + \log_5 \square = \log_5 (2 \cdot \square) \][/tex]
Given that it equals [tex]\(\log_5 14\)[/tex], we can equate:
[tex]\[ 2 \cdot \square = 14 \][/tex]
Solving for the missing value, we get:
[tex]\[ \square = \frac{14}{2} = 7 \][/tex]
So, (b) [tex]\(\log_5 2 + \log_5 7 = \log_5 14\)[/tex].
### (c) [tex]\(3 \log_3 2 = \log_3 \square\)[/tex]
We use the property of logarithms that states:
[tex]\[ n \log_b a = \log_b (a^n) \][/tex]
Applying this property, we have:
[tex]\[ 3 \log_3 2 = \log_3 (2^3) \][/tex]
Thus, the missing value in the equation is:
[tex]\[ \square = 2^3 = 8 \][/tex]
So, (c) [tex]\(3 \log_3 2 = \log_3 8\)[/tex].
### Summary of Solutions:
(a) [tex]\(\log_7 3 - \log_7 8 = \log_7 \left(\frac{3}{8}\right)\)[/tex]
(b) [tex]\(\log_5 2 + \log_5 7 = \log_5 14\)[/tex]
(c) [tex]\(3 \log_3 2 = \log_3 8\)[/tex]
We have filled in the missing values to make the equations true.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.